A REPORT ON MISSIONARY ACTIVITIES IN HEALT SEVICE IN THE SYRIA AND THE OPENING OF THE DAMASCUS FACULTY OF MEDICINE - Kürşat ÇELİK (Fırat University, 2019)
With the beginning of 19th century, missionaries started to work intensively in Ottoman Empire. First activities of missionaries began in Syria which was in the boundaries of Ottoman. Close to the holy places in this area, being away from supervision and audit of central government and being intersection of Asia, Africa and Europe were effective in the preference of the Middle East. Missionaries firstly engaged in education activities in the Syria. Educational activities have been followed by medical activities. Missioners took Jesus, who cure patients, as a reference for their activities in the medical works and they achieved their goal in a short time by performing health service and establishing close relationship with local community. There were mainly French and American missioners in the Syria. Beirut American Medical Faculty was established by Americans and St. Joseph Medical Faculty was established by French for training qualified employee in medical works. Missioners, who trained in these faculties, were sent to hospitals, dispensaries and pharmacy in various places especially cities in the Middle East. Ottoman Empire has planned to open the Damascus Faculty of Medicine to be an alternative to these institutions. Various reports on executive, politics, economics and education were written for revealing reasons of the situation, which Ottoman Empire had in his last period. After giving information about current situation, these reports also included recommendations on measures to be taken. Also there were other reports for revealing what kind of medical works which conducted by missioners in Syria and how these works carried out. In this study, Missionaries medical activities in the Syria and measures that government were going to take toward to these missionary activities are investigated according to the report which prepared by Syria Medical Inspectorship in 29 November 1892.